The Shift of Bacterial Sensitivity with Antibiotics in Acute Tonsillitis (Journal of Nobel Medical College, 2021)
Correction: The second author, Sanjib Mani Regmi, was added to the website version on 13th August 2021. It omitted by mistake. The PDF of the article was correct.Background: The infection of tonsil may occur primarily or secondarily as a result of upper respiratory tract infection, usually preceded by a viral infection. Bacterial tonsillitis is most commonly caused by Streptococcus pyogenes. Penicillin remains the treatment of choice for S. pyogenes tonsillitis. The present study aimed to identify the bacterial pathogen in acute tonsillitis and their sensitivity to antibiotics.Material and Methods: This prospective study was conducted in the Department of Otolaryngology and Head & Neck Surgery and Department of Microbiology, Gandaki Medical College, Pokhara Nepal from January 2018 to January 2019. Ninety-six patients who presented with acute tonsillitis and admitted in the hospital were included in the study.Results: The commonest age group of acute tonsillitis was found to be between 21-30 years. S. pyogenes was the commonest isolate 32(33.3%) followed by S. aureus 19(19.8%).  Streptococcus pyogenes was sensitive to Ampicillin (65.6%) and Cloxacillin (68.7%) while the isolates were more sensitive to levofloxacin and doxycycline. Carbapenem were found to be most effective drugs for intravenous treatment.Conclusion: The most common bacterial isolates were Streptococcus pyogenes. The sensitivity of organism shift from ampicillin group to fluroquinolones and tetracycline. Identification of bacterial isolates and their antibiotics sensitivity patterns could prevent resistance of bacteria to drugs and help in the proper management of acute tonsillitis.